2014
DOI: 10.1177/0956462414523260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of syndromic management of sexually transmitted infections within the Kisumu Incidence Cohort Study

Abstract: Summary Background While laboratory aetiological diagnosis is considered the gold standard for diagnosis and management of sexually transmitted infections, syndromic management has been presented as a simplified and affordable approach for sexually transmitted infection management in limited resource settings. Methods Sexually transmitted infection signs and symptoms were collected using staff-administered computer-assisted personal interview and audio computer-assisted self-interview. Participants underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…In the bivariate analysis, the use of any illicit drug in the past 12 months was a predictive variable for syphilis and is in agreement with other published studies (FAN et al, 2012;PAN et al, 2013;OTIENO et al, 2014). On the other hand, in multivariate analysis, only the realization of circumcision was considered statistically significant as a protective factor for syphilis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the bivariate analysis, the use of any illicit drug in the past 12 months was a predictive variable for syphilis and is in agreement with other published studies (FAN et al, 2012;PAN et al, 2013;OTIENO et al, 2014). On the other hand, in multivariate analysis, only the realization of circumcision was considered statistically significant as a protective factor for syphilis.…”
Section: Discussionsupporting
confidence: 79%
“…Other studies have demonstrated differences in the characteristics mentioned above in the studied populations (GUO et al, 2011;PAN et al, 2013). By another hand, in this study, the majority of attended individuals is not married, have had the first sexual relation with less than 16 years, has multiple partners and does not use condoms, these are common features in epidemiological studies of sexually transmitted diseases (FAN et al, 2012;OTIENO et al, 2014).…”
Section: Discussionmentioning
confidence: 78%
“…Our findings and that of other recent studies, however, question the validity of this approach based on the large proportion of asymptomatic STIs prevalent in pregnant and other high-risk population groups. 15,[24][25][26][27] When extrapolating our findings to all primary health clinics using the syndromic approach to treating STIs in women, it would appear that an estimated 50% of pregnant women with 1 or more STIs and asymptomatic will go untreated if the syndromic approach is applied. Postdelivery, an estimated 80% of the women who are asymptomatic but infected with 1 or more STIs would be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also showed predisposing factors for the incidences of chlamydia and candida including multiple sex partners within less than 30 days and sexual intercourse during menses in the previous 6 months 20 . Several studies have demonstrated that circumcision of men does not reduce their risk of acquiring these nonulcerative sexually transmitted infections like chlamydia and candidiasis 21 .…”
Section: Discussionmentioning
confidence: 99%